Juridical Analysis of Handling Non-Procedural Indonesian Migrant Worker Practices by the P4MI Parepare - Sunita Sunita; Wahyu Rasyid; Dodie Baltazar Taher Abejo (Universitas Muhammadiyah Mataram, 2025)
The author raised the title of the thesis